Kontribusi Testimoni dalam Meningkatkan Efektivitas Pendidikan Kesehatan tentang Napza di Kabupaten Sleman - Ririn Puspandari, IM Sunarsih, Rendra Widyatama (Berita Kedokteran Masyarakat (BKM), 2008)
Background: Drugs  abuse  including  narcotic,  alcohol,  psychotropic  and  other  addictive  elements  (Napza) keep  increased. Teenager  is  a  high  risky  group  toward  external  bad  influence  including Napza. The  increasing tendency  of  the  number  of  drugs  abuse  and  the  age  of  drug  user which  tend  to  be  younger,  demanded prevention  effort  and  appropriate  control. School  as  education  institution  is  an  appropriate  place  to  prevent drugs  abuse  by  giving  right  information  through  health  education. The  appropriate method  that  needs  to  be selected  should be  suitable with  situation and  condition  in  the  school  in order  to  create  an  optimum  result.Objective: Health  education  for  drugs abuse  through  speech with audiovisual,  speech  by  presenting  former  of user  (testimony) and  group discussion was expected  could  influenced  on  the  level of  knowledge and  changed student’s attitude  toward drugs  abuse prevention.  This  research was aimed  to  find  out  the  influence of  health education  through  speech with  audiovisual  as well  as  through  speech with  testimony  and group  discussion toward  knowledge and  attitude  of  students  in  the  prevention  of  drugs  abuse.Method: This was  a quasi  experimental  research  that used Solomon  four  group designs. The  research  subject was  consisted  of  two  treatment  groups  and  two  control  groups. The  data was  collected with  questioner regarding  knowledge  and  attitude. Data  processing  and  analysis was  used  student  t-test and  anova.Result:  There was  a knowledge  improvement on  the  first  treatment group  that used  interactive speech  and audiovisual as well as  in  the  second  treatment  group  that  used  interactive  speech method,  testimony and  group discussion  (p<0,05). There was  a  significant  improvement on  attitude  toward  drugs  abuse  prevention  in  the group with  interactive speech,  testimony, and  group discussion. There was  a difference  on  knowledge  between both  of  the methods  toward  improvement  on  attitude  and  yet  there was  a  difference  on  knowledge  toward knowledge  improvement.Keywords: health  education,  testimony,  knowledge,  attitude  and drugs  abuse